PENGARUH TARI MARTUMBA TERHADAP PENGETAHUAN KESEHATAN REPRODUKSI REMAJA DI SMA NEGERI 1 PARLILITAN KECAMATAN PARLILITAN KABUPATEN HUMBANG HASUNDUTAN TAHUN 2019 - Veronika Sinaga, Lia Rosa; Manurung, Jasmen; Hasugia, Silvia Oktaviyanti (EDUTECH CONSULTANT, 2019)
The result of the survey at SMA Negeri 1 Parlilitan in 2019 showed that adolescents’ level of knowledge of reproductive health was low which could cause sexual abuse, marriage in young age, unwanted pregnancy, narcotics, and PMS (sexual Transmitted Disease) since the young are susceptible to hoax. Lecture method and counseling tend to be tedious for students and inadequate knowledge for them. Therefore, health education with Martumba dance can be used as health promotion about reproductive health in adolescents at SMA Negeri 1 Parlilitan, Parlilitan Subditrict, Humbang Hasundutan Regency, in 2019. The research used quasi-experimental method with pretest-posttest one group only design. The samples were 62 students based on inclusion and exclusion criteria. The data were gathered by using questionnaires. The result of Wilcoxon test showed that p-value = 0.000 which indicated that there was significant difference in adolescents’ knowledge of reproductive health. In the pre-Martumba dance their mean-knowledge was 4,96 and in the post- Martumba dance it was 10.34 so that the disparity was 5.38. it is recommended that health promotion in adolescents be done more creatively by using different media in order to increase their knowledge as primary prevention.